La infografía informativa como estrategia didáctica para mejorar el aprendizaje en la competencia construye interpretaciones históricas de los estudiantes de la I.E. Isla del Tigre del nivel secundario Ramón Castilla 2022 - Herrera Cornejo, Carlos Miguel (2022)
This research has been carried out with the purpose of determining the effectiveness of informative infographics used as a didactic strategy to improve learning in the competition builds historical interpretations in the students of the Isla del Tigre Educational Institution of the Ramón Castilla secondary level. The type of research used in the study is applied by adopting the preexperimental design with pre-test and post-test. The population and sample that have been taken into account are 47 students from 1st to 5th grade of the secondary level of the Isla del Tigre Ramón Castilla educational institution. Data was obtained using the task analysis technique, with respect to the instrument used, this was a historical interpretation sheet, which was previously validated by experts. The research concluded that Informative Infographics as a didactic strategy to improve learning in competition builds historical interpretations is effective.